Global DNA-methylation in quantitative epigenetics: orbitrap mass spectrometry - Otto, Janine F. M.; Pohnert, Georg; Wichard, Thomas; Bauer, Michael; Busch, Anne; Ueberschaar, Nico (Frontiers in Molecular Biosciences, 2025)
DNA methylation is the most common epigenetic modification in both prokaryotic and eukaryotic genomes. Here we present a method based on highly efficient acid-hydrolysis of DNA, liquid chromatography, and detection by mass spectrometry to accurately quantify cytosine methylation in highly methylated DNA samples. This approach enables direct, rapid, cost-efficient, and sensitive quantification of the methyl-modified nucleobase 5-methylcytosine and 6-methyl adenine, along with their unmodified nucleobases. In contrast to standard sequencing techniques, our method only gives quantitative information on the overall degree of methylation, but it requires only small amounts of DNA and is not dependent on lengthy bioinformatic analyses. Our method allows rapid, global methylome analysis and quantifies a central epigenetic marker. In a proof-of-principle study, we show that it can also be extended to the monitoring of other DNA modifications, such as methylated adenine. Uncomplicated data analysis facilitates a quick and straightforward comparison of DNA methylation across biological contexts. In a case study, we also successfully identified changes in methylation signatures in the marine macroalga Ulva mutabilis “slender”. The advantage of global methylation analysis compared to sequencing allows for generating fast prior knowledge on which sample sequencing is senseful. The great benefit of the presented method is the speed and accuracy of the global methylation analysis, which is independent of the total methylation rate and gives accurate results, whereas competitive based on enzymatic digestion might fail.